Faktor-Faktor yang Mempengaruhi Keputusan Pembelian: (Studi Kasus pada WW Collection Pungging) - Amrulloh, Afif; Hartono, Hartono; Hidayat, M. Syamsul (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2025)
This study aims to examine and analyze the influence of Product Design, Product Quality, and Lifestyle on Purchase Decisions, with a case study at WW Collection in Pungging. A quantitative approach was employed, using surveys as the main data collection method. Questionnaires were distributed to respondents who had made at least one purchase, either through social media platforms or by visiting the store directly. The sampling technique used was purposive sampling, with a total of 385 respondents. Data analysis was conducted using SPSS software, applying the t-test to determine the effect of each variable on purchasing decisions. The results indicate that Product Design has a significant influence on purchase decisions. Likewise, Lifestyle also significantly affects consumers’ purchasing decisions. Additionally, Product Quality shows a positive and significant impact on purchase behavior. Simultaneously, all three variables: Product Design, Product Quality, and Lifestyle exert a meaningful influence on consumer purchasing decisions at WW Collection. These findings suggest that these factors play a crucial role in shaping consumer behavior and should be a key focus in WW Collection’s marketing strategies. By understanding and aligning with consumer preferences and lifestyles, the company can enhance its product appeal and customer satisfaction. Consequently, WW Collection is encouraged to maintain and improve these influencing factors to sustain competitiveness and drive consumer loyalty.